Mosaic and Trencadís in the Palau De La Música Catalana - Cristina Martí Robledo (Emerging Science Journal, 2018)
Modernism has provided Catalonia with buildings of great artistic value, such as the Palau de la Música Catalana located in the heart of Barcelona. Its architect, Lluís Domènech i Montaner, approached ornamentation as a thorough integration of arts and crafts: ceramic is treated as the ¨key¨ element, decorating the entire building while coating and protecting its internal metallic structure at the same time.During Modernisme, the classic mosaic technique, based on the use of small tiles (or tesserae) made of ceramics or glass paste, incorporated a new method called trencadís (A procedure carried out using irregular pieces of tiles fragmented randomly and put together in an abstract way).